The determinants of Chinese outward foreign direct investment - Buckley, Peter J; Clegg, L Jeremy; Cross, Adam R; Liu, Xin; Voss, Hinrich; Zheng, Ping (Journal of International Business Studies, 2007)
This study investigates the determinants of Chinese outward direct investment (ODI) and the extent to which three special explanations (capital market imperfections, special ownership advantages and institutional factors) need to be nested within the general theory of the multinational firm. We test our hypotheses using official Chinese ODI data collected between 1984 and 2001. We find Chinese ODI to be associated with high levels of political risk in, and cultural proximity to, host countries throughout, and with host market size and geographic proximity (1984–1991) and host natural resources endowments (1992–2001). We find strong support for the argument that aspects of the special theory help to explain the behaviour of Chinese multinational enterprises.